Post-obturation tooth discoloration: a scoping review of endodontic sealer choices for aesthetic success - Alhashimi, Raghad A; Gafita, George C; Martin, Dinesh (Journal of Baghdad College of Dentistry, 2025)
Background: Post obturation discoloration, is an undesirable outcome of endodontic treatment and is particularly burdensome on clinicians managing anterior teeth. Objectives: This review examines the discoloration potential of a plethora of historical and currently used endodontic sealers with the aim of providing clinicians with a guide on material selection, with the most minimal esthetic impact. Method: A PICO framework was employed to identify relevant data, focusing on discoloration associated with different sealers. A literature search was conducted across PubMed, ScienceDirect, and Google Scholar. Relevant studies published between January 2000 and January 2024 were selected based on pre-defined inclusion and exclusion criteria. The findings revealed that most of the included studies were ex vivo and in vitro, with limited in vivo evidence available. Insufficient long-term follow-up was noted and direct comparisons between the various sealer brands was limited. Conclusion: Zinc oxide-based sealers should be avoided by the clinician in areas of high esthetic concern. The strict confinement of the sealers to the canal space, is the best strategy to minimize discoloration. There is a need for improved materials, and more robust long-term studies to generate evidence-based guidelines as it relates to sealers.